PENGGUNAAN METODE CREATIVE PROBLEM SOLVING TERHADAP PEMBELAJARAN PESAWAT SEDERHANA UNTUK PENINGKATAN PEMAHAMAN KONSEP DAN KETERAMPILAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Yunus, Mardi; Fahyuddin, Fahyuddin; Safiuddin, La Ode (-)
Abstract. This study aimed to determine the mean score of improvement (N-`gain) in students’ understanding of concepts and creative thinking skill after they received instruction using creative problem-solving method and how significant it was when compared to the improvement made by their cohort who learnt via direct learning method, especially in their learning of simple airplane material. The sample of this research is 68 sixth grade students from elementary school of Integrated Islam Al Qalam Kendari where  they are distributed in two parallel classes (VA and VB). The VA class (N = 34) was randomly selected to be the experimental class (get Creative Problem Solving), while the VB class (N = 34) as the control class (get direct instruction). This study was a quasi experiment that using "pretest-postest control group designs.  It was found that the students who used the creative problem solving mtehods scored significantly higher than those attended direct instruction toward  conceptual understading and creative thinking skills. However, based on sub-materials, conceptual comprehension indicators,and creative thinking skills indicators there were variaties for the learning of creative problem solving methods over to direct instruction. Keywords: Instructional Design, Creative Problem Solving, Direct Instruction,                 Conceptual Understanding, Creative Thinking Skills